Analisa Risiko Rantai Pasok Produk Kosmetik Sistem Make to Order Dengan Metode House of Risk - Glory Riama Hosianna; Sawarni Hasibuan; Juliza Hidayati (Universitas Mercu Buana, 2021)
Risk is a factor that hinders supply chain operations that cannot be avoided but can be minimized or eliminated by carrying out appropriate risk management. This research was conducted at a cosmetic factory with a make-to-order business system. The purpose of this research is to identify the various risks that occur, analyze the sources of risk and create mitigation strategies. The method used in this research is the House of Risk Model to identify and determine the priority of the handling strategy. There are 7 risks that become a priority for mitigation, namely sudden demand, increased demand, dependence on one supplier, supplier lead time too long, delays in delivery schedules, inappropriate alternative supplier selection, and delays in the purchasing process. In this case, the planning and sourcing processes must be improved.